Bisphenol A as a Factor in the Mosaic of Autoimmunity - Lazurova, Zora; Lazurova, Ivica; Shoenfeld, Yehuda (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
The population worldwide is largely exposed to bisphenol A (BPA), a commonly used plasticizer, that has a similar molecular structure to endogenous estrogens. Therefore, it is able to influence physiological processes in the human body, taking part in pathophysiology of various endocrinopathies, as well as, cardiovascular, neurological and oncological diseases. BPA has been found to affect the immune system, leading to the development of autoimmunity and allergies, too. In the last few decades, the prevalence of autoimmune diseases has significantly increased that could be explained by a rising exposure of the population to environmental factors, such as BPA. BPA has been found to play a role in the pathogenesis of systemic autoimmune diseases and also organ-specific autoimmunity (thyroid autoimmunity, diabetes mellitus type 1, myocarditis, inflammatory bowel disease, multiple sclerosis, encephalomyelitis etc), but the results of some studies still remain controversial, so further research is needed.
Keywords: autoimmune diseases